A new "naked-eye" colorimetric and ratiometric fluorescent sensor for imaging Hg2+ in living cells. Issue 48 (29th November 2019) - Yin, Pengcheng; Niu, Qingfen; Yang, Qingxin; Lan, Linxin; Li, Tianduo
Abstract: A new oligothiophene-based sensor 3 TH for monitoring Hg 2+ has been designed and synthesized based on the intramolecular charge transfer (ICT) mechanism. The 3 TH shows the significant specificity toward Hg 2+ through "naked-eye" colorimetric detection as well as via ratiometric fluorescence enhancement response with low detection limit of 62 nM. In addition, sensor 3 TH shows high selectivity and sensitivity for Hg 2+ with fast response in a suitable pH range. Moreover, the 3 TH -based test strips was used to conveniently detect Hg 2+ ions in water. Furthermore, considering its good ''turn-on'' fluorescent sensing behavior and low cell cytotoxicity, 3 TH was successfully applied to detect and image Hg 2+ in real water samples and living cells, which shows great potentials for application in environmental and biological systems. Graphical abstract: Image 1 Highlights: A novel naked-eye colorimetric and turn-on ratiometric fluorescent sensor 3 TH for Hg 2+ was developed. 3 TH towards Hg 2+ features good selectivity, high sensitivity, fast response in a wide pH range. 3 TH shows low cytotoxicity and excellent ''turn-on'' fluorescent sensing properties. 3 TH was used to detect and image Hg 2+ in water, test strips and living cells.